ChemInform Abstract: One‐Pot Synthesis of 3‐Hydroxyanthranilate Derivatives Using Furans, Bromoalkyne, and Secondary Amines. Issue 34 (August 2015) - Shinohara, Hiroyuki; Sonoda, Motohiro; Hayagane, Naoya; Kita, Shota; Okushima, Shunsuke; Tanimori, Shinji; Ogawa, Akiya
Abstract The synthesis of 3‐hydroxyanthranilate derivatives is achieved through Diels—Alder reaction of furans with alkyne (II), followed by conjugate addition of amine, dehydrobromination, and a ring‐opening aromatization reaction.